The Role of Trust in Moderating The Effect of Feel Experience on Repurchase Intention - Gunawan, Made Willy; Widagda K, I Gusti Ngurah Jaya Agung (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This study investigates how customers' emotional experience with Richeese Factory affects their willingness to repurchase from the restaurant chain and further explores the moderating role of trust in this relationship. This research is also expected to significantly contribute to the restaurant industry's efforts to increase customer loyalty through positive emotional experiences. Method: This study used non-probability sampling with purposive sampling. The sample size was 100 respondents. Data was collected through an online questionnaire distributed through Google Forms. Moderated Regression Analysis with SPSS 26 software was used to analyze data and test hypotheses. Research Findings: This study found a positive and significant relationship between felt experience and repurchase intention. This suggests that customers with a positive emotional experience at Richeese Factory are more likely to return. Trust in Richeese Factory acts as a moderating variable, strengthening the positive effect of feel experience on repurchase intentions. In simpler terms, customers with a positive emotional experience and trust Richeese Factory are more likely to make repeat purchases. Theoretical Contribution: This research is expected to expand insights and knowledge related to the influence of trust in moderating the relationship between felt experience and repurchase intentions. It will also significantly contribute to the restaurant industry's increase in customer loyalty. Practical Implications: This study shows that improving customer emotional experiences and building trust can increase repurchase intentions. However, further research could study factors such as service quality, food taste, or restaurant atmosphere that contribute to positive emotional experiences. Research Limitations: This study used a non-probability sampling method because the population size is uncertain. This limits the generalizability of the findings to the entire Richeese Factory customer base in Denpasar City.